Digital Competence Is The Basis Of A Successful Teacher's Activity - Artikova Muhayyo Botiraliyevna (Researchparks Publishing, 2023)
The article is devoted to the description of digital competencies of teachers working in the field of modern education. The article presents a certain structure of digital competencies, their analysis and a set of basic competencies that help to carry out successful pedagogical activities.